2017
DOI: 10.1016/j.foodres.2016.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of yeast inoculated during semi-dry coffee fermentation and the effect on chemical and sensorial properties of the final beverage

Abstract: Pulped Mundo Novo and Ouro Amarelo coffee beans were inoculated with Saccharomyces cerevisiae (CCMA 0200 and CCMA 0543) during semi-dry coffee fermentation and compared with a non-inoculated control. Samples were collected throughout the fermentation process (12days) to evaluate the persistence of the inoculum by Real-Time quantitative PCR (qPCR). Also, the chemical composition of the beans was determined by HPLC and GC-MS and the roasted beans were sensorial evaluated using the cupping test. S. cerevisiae CCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 16 publications
1
44
0
4
Order By: Relevance
“…Mundo Novo was characterized by caramel, herbaceous, brown sugar, and honey flavors and aromas. Other studies also showed that the starter yeast promoted coffee quality and that the same strains started to behave differently according to the coffee variety due to different sugar concentrations found in the coffee varieties …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mundo Novo was characterized by caramel, herbaceous, brown sugar, and honey flavors and aromas. Other studies also showed that the starter yeast promoted coffee quality and that the same strains started to behave differently according to the coffee variety due to different sugar concentrations found in the coffee varieties …”
Section: Resultsmentioning
confidence: 99%
“…The following samples were analyzed: pulped coffee at the start of fermentation, coffee without mucilage (demucilated coffee) at the end of fermentation, and dried coffee at the final drying time. Samples were prepared according to Ribeiro et al 6 The extracts were analyzed using a high-performance liquid chromatography system (Shimadzu, Japan). A Shimpack SCR-101H (7.9 mm × 30 cm) column was used with a 100 mM solution of perchloric acid with a flow rate of 0.6 mL min −1 as the mobile phase.…”
Section: Analysis Of Acids and Sugars By High-performance Liquid Chromentioning
confidence: 99%
See 3 more Smart Citations